2020
DOI: 10.3389/fnins.2020.575459
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Neurorestorative Effects of Holothuria scabra Extract in the MPTP/MPP+-Induced Mouse and Cellular Models of Parkinson’s Disease

Abstract: Extracts from Holothuria scabra (HS) have been shown to possess anti-inflammation, anti-oxidant and anti-cancer activities. More recently, it was shown to have neuroprotective potential in Caenorhabditis elegans PD model. Here, we assessed whether HS has neuroprotective and neurorestorative effects on dopaminergic neurons in both mouse and cellular models of PD. We found that both pre-treatment and post-treatment with HS improved motor deficits in PD mouse model induced with 1-methyl-4-phenyl-1,2,3,6-tetrahydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Regarding PD, Holothuria scabra, through its bioactive compounds, has shown promise, as well as Xylaria sp., since both seem to attenuate the degeneration of dopaminergic neurons (Li et al, 2013;Lu et al, 2010;Chalorak et al, 2018;Chalorak et al, 2021). Furthermore, Holothuria scabra was able to reduce alpha synuclein deposition, while Xylaria sp., with its metabolite Xyl-B, reduced the formation of Mhtt protein aggregates, suggesting a possible neuroprotective effect for HD (Noonong et al, 2020;Zeng et al, 2016). The other marine compounds present in this study show promising potential in the context of ND, however further studies are needed for a better understanding of the repercussion of these compounds in the course of ND.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Regarding PD, Holothuria scabra, through its bioactive compounds, has shown promise, as well as Xylaria sp., since both seem to attenuate the degeneration of dopaminergic neurons (Li et al, 2013;Lu et al, 2010;Chalorak et al, 2018;Chalorak et al, 2021). Furthermore, Holothuria scabra was able to reduce alpha synuclein deposition, while Xylaria sp., with its metabolite Xyl-B, reduced the formation of Mhtt protein aggregates, suggesting a possible neuroprotective effect for HD (Noonong et al, 2020;Zeng et al, 2016). The other marine compounds present in this study show promising potential in the context of ND, however further studies are needed for a better understanding of the repercussion of these compounds in the course of ND.…”
Section: Discussionmentioning
confidence: 81%
“…In another study, Chalorak et al (2021) showed reduced a-synuclein accumulation in dopaminergic neurons after treatment with diterpene glycosides extracted from Holothuria Scabra (Figure 3A and 3B) (Chalorak et al, 2021). Noonong et al (2020) also evaluated the neuroprotective effect of Holothuria scabras metabolites (MHS-Friedelina, 3-hydroxybenzaldehyde, and 4-hydroxybenzaldehyde) in mice that were induced in PD by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, and showed neurorestorative effects in motor deficiencies, in addition to a significant increase in the cell viability of dopaminergic neurons, promoting the synthesis of tyrosine hydroxylase (TH) and suppressing the formation of α-synuclein protein (Noonong et al, 2020). Finally, the study by Tangrodchanapong et al (2021) demonstrated the effect of the cyclic ether 2-butoxytetrahydrofuran (2-BTHF), which presented a neuroprotective action by learning and memory deficits in a murine model of dementia (Che et al, 2017).…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…24 Furthermore, H. scabra extract was found to decrease α-synuclein formation induced by MPP + -induced SH-SY5Y cell apoptosis through alterations in cellular metabolism, resulting in the enhancement of tyrosine hydroxylase (TH)-stained DAergic neurons. 25 As a result, it is possible that 2-BTHF derived from H. scabra could alleviate α-synuclein-mediated toxicity, leading to an improvement in the GFP-tagged area of CEP DAergic neurons in the UA44 strain.…”
Section: -Bthf Mitigated α-Synuclein-induced Daergic Neurodegeneratio...mentioning
confidence: 99%
“…32 The deficiency in dopamine signaling, resulting from the absence of TH, is characterized by impaired dopaminedependent behaviors. 33 Importantly, the H. scabra extract was demonstrated to boost TH, 25 the rate-limiting enzyme in catecholamine biosynthesis. This enzyme catalyzes the hydroxylation of tyrosine to L-DOPA within the dopamine signaling pathway.…”
Section: -Bthf Decreased the Aggregation-prone Monomeric α-Synuclein ...mentioning
confidence: 99%